2023
DOI: 10.1021/acs.est.2c09082
|View full text |Cite
|
Sign up to set email alerts
|

Internal Biofilm Heterogeneities Enhance Solute Mixing and Chemical Reactions in Porous Media

Abstract: Bacterial biofilms can form in porous media that are of interest in industrial applications ranging from medical implants to biofilters as well as in environmental applications such as in situ groundwater remediation, where they can be critical locations for biogeochemical reactions. The presence of biofilms modifies porous media topology and hydrodynamics by clogging pores and consequently solutes transport and reactions kinetics. The interplay between highly heterogeneous flow fields found in porous media an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…These conclusions are illustrated in Figure , which summarizes the mass balance of the various processes controlling the UVF fate of BP-3 and its TPs in the CT (a similar figure for the ST is shown in Figure S5), which underscores the central role of biofilm in the fate of UVFs. This aligns perfectly with the findings in the recent study by Markale et al, where they observed a significant impact of biofilm permeability heterogeneity on biologically driven reactions …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These conclusions are illustrated in Figure , which summarizes the mass balance of the various processes controlling the UVF fate of BP-3 and its TPs in the CT (a similar figure for the ST is shown in Figure S5), which underscores the central role of biofilm in the fate of UVFs. This aligns perfectly with the findings in the recent study by Markale et al, where they observed a significant impact of biofilm permeability heterogeneity on biologically driven reactions …”
Section: Resultssupporting
confidence: 93%
“…This aligns perfectly with the findings in the recent study by Markale et al, where they observed a significant impact of biofilm permeability heterogeneity on biologically driven reactions. 48 Overall, this study demonstrates that implementing a reactive barrier in an infiltration basin improves the degradation of benzophenone-type UVFs and, especially, of BP-3 and its TPs, and that biofilm acts as an additional environmental compartment favoring the retention and degradation of UVFs in porous media. It does not sway us that these processes can be assumed for other hydrophobic compounds.…”
Section: Retention Of Uvfs In Immobilementioning
confidence: 58%
See 1 more Smart Citation
“…This is an important distinction to microbial growth in porous media (such as soils, sediments, aquifers, or engineered systems like packed bed reactors or trickling filter systems in wastewater treatment) where numerical studies of the interaction between the biofilm surface roughness and mass transport ( 27 ) and simulations of coupled microbial growth and flow in porous media ( 28 32 ) have provided key insights on how flow can shape localized growth conditions. However, in contrast to the microenvironments we focus on in this study, microbial communities in porous media attach to the solid structures and create streamers that can clog macropores ( 33 , 34 ) and alter preferential flow paths within the porous media with consequences for nutrient supply ( 35 , 36 ). Thus, although similarities exist between the systems, caution needs to be exerted when extrapolating insights from our analysis to other porous media.…”
Section: Discussionmentioning
confidence: 99%
“…Most of prior investigations have selected theoretical methods about fine aggregate cementation based on the MICP technique. According to the MICP process, these methods can be categorized into four parts: the distribution and transport of biomass, biochemical reaction, MICP solidification, and CaCO 3 precipitation [33][34][35][36][37][38][39]. These parts can affect the ultimate impact of biocementation.…”
Section: Introductionmentioning
confidence: 99%